ANALISIS PREFERENSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN ES KOPI SUSU (STUDI KASUS PADA KONSUMEN OMBE KOFIE SUMMARECON MAL BEKASI) - Donovan, Jessen; Hurdawaty, Ramon (Jurnal Pendidikan dan Perhotelan (JPP), 2022)
Coffee served in a coffee shop does not only sell the taste and type of coffee because in a coffee shop there are other attributes. Attributes of coffee shops such as location, facilities, and infrastructure, the atmosphere of the coffee shop are also thought to influence coffee consumers' preferences for visiting and consuming coffee. Consumer preferences will influence the purchasing decisions of coffee consumers. Knowing consumer preferences is one of the strengths of each coffee shop to be able to face competition in the long term. The purpose of this study is to determine consumer preferences in buying iced milk coffee and also want to find out from the preferences that exist, which preference factors are most considered by consumers in deciding to buy the product. This research is a quantitative study using descriptive methods and survey techniques. For the sampling method used in this study is the purposive sampling method. The data collection method used a questionnaire distributed to 91 respondents, which will be analyzed using the chi-square test and also multi-attribute fishbein. Attributes of consumer preferences in this study which refer to several previous studies have been determined by the author, the attributes of taste, price, brand, and packaging. Chi-square test results if X2 count > X2 table, then the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, that with the results of X2 count all items of consumer preference attributes are greater than X2 tables, then Ho is rejected and Ha is accepted. By multiplying the confidence number (bi) and also the evaluation (ei), the consumer attitude index (Ao) is obtained, where the results can be sorted from the most considered are taste, price, packaging, and brand.